The impact of restorative material and ceramic thickness on CAD\CAM endocrowns - Tribst, João-Paulo-Mendes [UNESP]; de Oliveira Dal Piva, Amanda-Maria [UNESP]; Madruga, Camila-Ferreira-Leite [UNESP]; Valera, Marcia-Carneiro [UNESP]; Bresciani, Eduardo [UNESP]; Bottino, Marco-Antonio [UNESP]; de Melo, Renata-Marques [UNESP] (Medicina Oral, S.L., 2019)
Background: Endocrown restorations as a conservative approach to restore endodontically treated teeth still need an in vitro investigation under fatigue at different materials. This study evaluated the effect of restorative material and restoration thickness on the maximum fracture load of endocrowns subjected to cyclic loading. Material and Methods: Sixty (60) third molar teeth received an endocrown preparation with three different heights of remaining dental tissue (1.5, 3.0 or 4.5 mm). A leucite-based ceramic (LEU) and a lithium disilicate (LD) based ceramic were selected to manufacture the CAD/CAM endocrown restorations, totaling 6 groups (n=10). The specimens were subjected to fatigue loading (200N, 2 x 106 cycles, water) and then to the single load to failure test (1 mm/min crosshead speed). Data were analyzed by using two-way ANOVA and Tukey tests (p < 0.05). Results: All endocrowns survived the fatigue test. The thickness did not influence the restoration's fracture load (p=0.548) instead the restorative material (p=0.003). LD showed higher mean values (1714.43 N)A than LEU (1313.47 N)B. Conclusions: Endocrowns manufactured with CAD/CAM lithium disilicate blocks showed superior fracture load than the leucite-based blocks after mechanical fatigue. Nevertheless, both materials presented acceptable survival and fracture load as long as the material's minimum thickness and the enamel adhesion are respected.
Keywords: CAD/CAM; Endocrown; Endodontically treated teeth; Failure load; Minimal intervention dentistry